Dietary hybrid phytase and carbohydrases on nutrient digestibility and bone quality of broiler chickens - Bavaresco, Caroline; Krabbe, Everton Luis; Surek, Diego; Gopinger, Edenilse; Martinez, Fernando Nicolas; Wernick, Bruno; Roll, Victor Fernando Büttow (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the effect of the use of hybrid phytase, alone or combined with carbohydrases, in poultry diets with nutritional reductions of calcium, available phosphorus, and metabolizable energy on the nutrient digestibility and bone quality of broiler chickens. A total of 1,875 broilers were distributed in five treatments in a completely randomized design, with 15 replicates of 25 chickens each. The treatments consisted of a positive control feed (T1) and of four negative controls (T2 to T5): T1, basal diet (BD) with corn and soybean; T2 and T3, BDs with reductions of 70 and 100 kcal kg-1 metabolizable energy, respectively, and both with reductions of 0.16% Ca and 0.15% available P; and T4 and T5, BDs with the same nutritional reductions, but supplemented with enzymes, i.e., T4 = T2 + 500 phytase units (FTU) per kilogram and T5 = T3 + 500 FTU kg-1 + 560 xylanase units (TXU) per kilogram + 250 glucanase units (TGU) per kilogram. The use of 500 FTU kg-1 hybrid phytase in pelleted corn-soybean meal diets allows a good digestive performance by broilers and replaces the nitrogen-corrected apparent metabolizable energy at 70 kcal kg-1, as well as 0.16% Ca and 0.15% available P.